Antidiabetic Effect of Memecylon Talbotianum Leaf Methanol Active Fraction in Male Wistar Rats - T.R., Bharathi; Jameel, Noor Mohamed; Ghassam, Behrouz Jalali; Bajpe, Shrisha Naik; HS, Prakash (Pharmacognosy Communications)
Introduction: Memecylon talbotianum Brandis, (Melastomataceae) is an indigenous medicinal plant used in ethno-medicine including Ayurveda. However, the potential of this plant in controlling diabetes has not yet been evaluated. The role of M. talbotianum leaf extract on streptozotocin (STZ, 2-deoxy-2-(3- (methyl-3-nitrosoureido) d-glucopyranose- induced diabetes in male Wistar rats is investigated. Methods: The leaf extract was fraction- ated, its phytoconstituents were evaluated using HPLC and rats (6 animals in each group) were treated orally with M. talbotianum leaf methanol active fraction (MTLMAF) (100, 200 and 1000 mg/kg body weight) for 28 days with a single dose with metformin as a positive control. Biochemical parameters, histopathological and immunostaining studies were performed. Results: Administration of MTLMAF, significantly decreased the glucose level after four weeks (312 ± 14 mg/dL in diabetic animals compared to 134 ± 13 mg/dL in MTLMAF treated animals) and controlled the levels of TG (155 ± 63.55 units/dL in diabetic and 100.66 ± 13.31 units/dL in treated animals), LDL, HDL, VLDL and endogenous antioxidants (SOD, catalase and GSH). Histopathological studies substantiated the protective role of MTLMAF. MTLMAF also alleviated liver and pancreatic damage in STZ- diabetic rats. HPLC analysis revealed that rutin, quercetin and protocatechuic acid were the major components present in M. talbotianum. The presence of these compounds in M. talbotianum is reported for the first time here and these compounds may be responsible for antidiabetic properties. Conclusion: Our study shows that MTLMAF could protect rats against streptozotocin induced diabetes, improves lipid profile, reduce the risk of oxidative stress and, ameliorate liver and pancreatic damage.
Keywords: HPLC; STZ-diabetes; M. talbotianum; MTLMAF; Antidiabetic